In silico Investigation of the Pro-apoptotic Potential of Syringic Acid Analog - Hosseini, Hossein; Khorasani, Reza Rajaie; Ketabi, Sepideh; Nikmaram, Farrokh Roya (Letters in Drug Design & Discovery, 2024)
BackgroundConformational changes in BAX are associated with the activation of its pro-apoptotic potential. Previously, small molecule BAX antagonists have been shown to bring about apoptosis by inducing conformational changes in BAX by direct binding to the serine 184 site of BAX.MethodsIn this article, we have proposed that syringic acid analog SA14 can incur apoptosis by directly binding to and inducing conformational changes in BAX. The pro-apoptotic potential of SA14 has been investigated using an in silico structure-based approach, i.e., docking and molecular dynamics computations are employed to study the binding of SA14 to the residues of the active site of BAX.ResultsBased on docking results, four BAX-SA14 complexes, each representative of a cluster of conformations, have been selected for molecular dynamics simulations. The root mean square deviation has indicated the formation of stable conformations for two of the complexes. Other parameters, such as root mean square fluctuation, radius of gyration, and solvent accessible surface area, have been used to confirm the results, which have indicated favorable binding between BAX and SA14.ConclusionOverall, the results have indicated that SA14 can bring about stable conformational changes in BAX and shows merit as a potential BAX-activating pro-apoptotic agent worthy of further experimental studies.
Keywords: molecular dynamics